30.5k views
5 votes
What is the missing term? (10x – 4x2) – (7x + ?) = 3x – 6x2

2 Answers

3 votes

Let

b----------> the missing term

we have


(10x - 4x^(2) )- (7x + b) = 3x - 6x^(2)

Combine like terms in the left side


(10x-7x)+(-b - 4x^(2)) = 3x - 6x^(2)


(3x)+(-b - 4x^(2)) = 3x - 6x^(2)

Simplify


(-b - 4x^(2)) = - 6x^(2)


b = 6x^(2)-4x^(2)


b = 2x^(2)

therefore

the answer is

the missing term is equal to
2x^(2)

User Rjcarl
by
5.5k points
2 votes
10x-4x^2-(7x+y)=3x-6x^2

2x^2+7x=7x+y

2x^2=y

check...

(10x-4x^2)-(7x+2x^2)=3x-6x^2

3x-6x^2=3x-6x^2

1=1

correct
User Arul Rozario
by
6.4k points